Islamic tradition in Ulu inscription and manuscript at Pasemah, South Sumatra, Indonesia: Tradisi Islam dalam prasasti dan naskah Ulu di wilayah Pasemah, Sumatera Selatan, Indonesia - Andhifani, Wahyu Rizky; Ali, Nor Huda (BRIN, 2021)
Ulu is a script developed in the southern part of Sumatra. The origin of the word ulu interpreted as upstream of a river or a highland. Ulu scripts are no longer used in the present era. Nevertheless, this paper examines the Islamic tradition in the Pasemah area based on the contents of Ulu manuscripts and inscriptions. The research objective is to discover the Islamic tradition in the contents, while the research purpose is to identify the influence of Islamic tradition towards the content. The research method includes data processing (source study, interview, and literature study), description of scale, origin, owner, state or condition, language, variation of characters, transliteration, translation, interpretation, synthesis, and data presentation. The result shows that the contents of Ulu manuscripts and inscriptions have intensely been influenced by Islamic tradition. The influence of Islam in Ulu manuscripts or inscriptions can also be comprehended from the public opinion towards it, categorized as profane, semi-sacred, and sacred.